MEKANISME REKRUTMEN PERANGKAT DESA - Feny Saidah Fitrianty; Rahman Amir; Sofyan Alhadar (Jurnal Administrasi, Manajemen dan Ilmu Sosial, 2022)
This study aims to determine the recruitment mechanism for village apparatus in Barakati Village, Batudaa District, Gorontalo Regency. The research method uses a descriptive qualitative approach. Data collection techniques were carried out through in-depth interviews with a number of informants, observation and recording of secondary data related to research problems. The results of the study concluded that the establishment of a village apparatus recruitment committee in Barakati Village had never been carried out. The selection of village apparatus recruitment files in Barakati Village has never been carried out. The village apparatus recruitment interview test in Barakati Village was not in accordance with the mechanism. The process of determining village officials in Barakati Village is not in accordance with the mechanism. Overall, it can be concluded that the mechanism for recruiting village officials in Barakati Village is concluded to be not optimal. This can be seen from the recruitment process for village officials which did not involve village officials in the recruitment process for new village officials, the file selection process was not carried out, there were no interviews for prospective village officials and the village apparatus appointment process was carried out unilaterally. It is suggested that in order to create a village government system that is clean and has good skills, it is necessary to select candidates for village apparatus in an open manner by forming committees, conducting file selection, carrying out interview stages and determining village apparatus candidates transparently.